2021
DOI: 10.17275/per.21.28.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Motivation in the classroom

Abstract: The aim of this research is to determine the factors affecting students' motivation. For this purpose, a model consisting of four dimensions has been created by scanning the literature, and the created model has been supported by the opinions of the participants. The research was carried out with qualitative method. The research was conducted in accordance with the "case study" design. In this context, this research was conducted in accordance with the case study design in terms of revealing the motivational e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The student's motivation in the classroom is affected by several factors, some of which are related to the teaching and learning process and the strategies and techniques used therein, including those related to the lesson and the study material. Other factors are related to the method of assessment and to the educational environment and materials used in teaching [54]. Schwan [55] confirmed that students' motivation increases when they are allocated a certain level of independence in their learning and allowed to make choices that support their goals.…”
Section: Motivation To Learnmentioning
confidence: 96%
“…The student's motivation in the classroom is affected by several factors, some of which are related to the teaching and learning process and the strategies and techniques used therein, including those related to the lesson and the study material. Other factors are related to the method of assessment and to the educational environment and materials used in teaching [54]. Schwan [55] confirmed that students' motivation increases when they are allocated a certain level of independence in their learning and allowed to make choices that support their goals.…”
Section: Motivation To Learnmentioning
confidence: 96%
“…In order for students to be involved in learning activities, the subject matter must be delivered more attractively (Ditta et al, 2020). This is because the delivery of interesting material can affect students' motivation to learn (Kılıç, 2021). When digital media is used properly it will produce a good understanding for students (Hobbs, 2013).…”
Section: Pembahasanmentioning
confidence: 99%
“…When students' participation motivation is low, negative learning behaviour can be seen most of the students with low motivation are unable to concentrate on the sub-ject, are bored with the lesson and have no idea about the ease of use of the issue. lacks imagination (Kılıç, M. E., Kılıç, M. Y., & Akan, D. 2021). Also, to stimulate students' internal motivation, it is recommended that foreign language teachers, whenever possible and wherever, focus on two forms of positive external motivation -identification and integration, and use less of two forms of negative external motivation -external regulation and introjection.…”
Section: Discussionmentioning
confidence: 99%